ECB Interventions in Distressed Sovereign Debt Markets: The Case of Greek Bonds - Christoph Trebesch; Jeromin Zettelmeyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study central bank interventions in times of severe distress (mid-2010), using a unique bond-level dataset of ECB purchases of Greek sovereign debt. ECB bond buying had a large impact on the price of short and medium maturity bonds, resulting in a remarkable twist of the Greek yield curve. However, the effects were limited to those sovereign bonds actually bought. We find little evidence for positive effects on market quality, or spillovers to close substitute bonds, CDS markets, or corporate bonds. The interventions thus had very local effects only, consistent with theories of segmented bond markets.
Keywords: E43; E58; F34; 330